2022
DOI: 10.3389/fmicb.2022.846215
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Role of Rac1 Glucosylation in Clostridioides difficile Toxin B-Induced Arrest of G1-S Transition

Abstract: Clostridioides difficile infection (CDI) in humans causes pseudomembranous colitis (PMC), which is a severe pathology characterized by a loss of epithelial barrier function and massive colonic inflammation. PMC has been attributed to the action of two large protein toxins, Toxin A (TcdA) and Toxin B (TcdB). TcdA and TcdB mono-O-glucosylate and thereby inactivate a broad spectrum of Rho GTPases and (in the case of TcdA) also some Ras GTPases. Rho/Ras GTPases promote G1-S transition through the activation of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…However, one should cautiously evaluate toxin effects in different species instead of extrapolating results from one species to another. Human organoid and/or intestinal epithelial systems have been used previously to assess the effects of TcdA and TcdB [ 45 , 46 , 53 ]. Using 2D and 3D approaches on canine intestinal organoids, we showed that toxin effects are not the same in small and large intestinal-derived organoids, even from the same species, so results from human studies may not be transferred directly to other organisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, one should cautiously evaluate toxin effects in different species instead of extrapolating results from one species to another. Human organoid and/or intestinal epithelial systems have been used previously to assess the effects of TcdA and TcdB [ 45 , 46 , 53 ]. Using 2D and 3D approaches on canine intestinal organoids, we showed that toxin effects are not the same in small and large intestinal-derived organoids, even from the same species, so results from human studies may not be transferred directly to other organisms.…”
Section: Discussionmentioning
confidence: 99%
“… 237 , 238 TcdB of C. difficile infection of HIOs inhibits stem cell repair capacity and delays epithelial cell renewal. 249 Infection with the major foodborne enteric pathogen Listeria affects goblet and paneth cell numbers, upregulates muc2 and lyz expression, and reduces the expression of genes related to the Notch pathway. Increased secretion of proinflammatory cytokines disrupts organoid morphology.…”
Section: Microecosystem Research Using Digestive Organoidsmentioning
confidence: 99%
“… 248 Clostridioides difficile Toxin B (TcdB) infection of HIOs inhibits stem cell repair capacity and delays epithelial cell renewal. 249 Colonization of Helicobacter pylori is associated with GC, which causes most gastric ulcers by inducing hypersecretion of gastric acid. 250 252 Gastric organoids from different sources have been used to replicate pathological conditions in vivo and to robustly mimic the gastric epithelial response to H. pylori infection in an in vitro system.…”
Section: Microecosystem Research Using Digestive Organoidsmentioning
confidence: 99%